CYBER INSURANCE: MODERN REQUIREMENTS - Ludmila Gumenyuk (Izdevnieciba "Baltija Publishing", 2021)
The purpose of this article is to outline current trends in the development of cyber insurance in the world and in Ukraine. Modern information wars and a significant increase in cyber-attacks over the past three years (2019-2021) indicate a low level of protection of critical infrastructure, data storage and personal information, so the development of cyber insurance as an effective protection tool is a priority today. Methodology. The article used methods of data analysis and synthesis to prepare the information base for defining the concept of cyber insurance; comparison of domestic and foreign publications to describe key features of cyber insurance; scientific induction and deduction to create recommendations for the spread of cyber insurance. Results. The results of the study indicate a high degree of danger of cyber risks in the modern world, as their variety is growing exponentially. That is why an effective mechanism for protecting the data of states, authorities, businesses and individuals must include cyber insurance. In addition, insurance companies need to develop policies with an individualized approach to each client, because the characteristics of digital behavior and the security state of the IT structure may differ. Practical implications. The article substantiates the provision of services to create an effective set of services against cyber risks and proposes a mechanism of interaction between insurance market participants on the vector of cyber insurance. The article classifies the main types of cyber risks for the business segment and individual clients, highlighting the most critical and dangerous ones. Value/originality. The results of the study allow insurance companies to create relevant products, prepare customers for modern challenges and prevent cyber-attacks, and government agencies to regulate relations in the field of cyber insurance.